Pengaruh Pemasangan Sudu Pengarah dan Variasi Jumlah Sudu Rotor terhadap Performance Turbin Angin Savonius - Ully, Dedy Nataniel; Soeparman, Sudjito; Hamidi, Nurkholis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
The objectives of research were to understand the influence of the installation of guide vane on the performance of Savonius wind turbine and to acknowledge the number of rotor blade which produces the most maximum performance. There are three variations for the number of rotor blade, which are 2, 3 and 4 blades on the range of wind speed are 4-7 m/s. Result of research indicated that rotor with three blades can give better performance than rotor with two and four blades. Rotor with guide vane has produced better performance in power coefficient rate for 0,3638 at wind speed 5 m/s, while rotor without guide vane can only provide power coefficient for 0,2595 at similar wind speed 5 m/s.Keywords: Wind Energy, Savonius Wind Turbine, Guide Vane and Performance